Fotografias de Sebastião Salgado: grafia, poética e produção do espaço geográfico - Sousa Pidner, Flora; Auxiliadora da Silva , Maria (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
The subject of the research is the Geography of Sebastião Salgado´s photographs. With attentive glances, the feelings that emerge from readings of these imagery photographs are intriguing: excitement for the beauty of the image; for the sadness and, at the same time, for the hope expressed by the photographed people. These photographs remind the meanings of space and time and thus, the contradictions, injustices and spatial-social conflicts. The goal is to interpret the photographs, for besides his sagacious beauty, in search of the unseen image, in other words, of a reality that does not end in appearance. The geographical categories landscape and place are the theoretical bases defined for the understanding of Salgado´s photographs, as spellings, as a poetic and as a way of producing the geographical space. The photographic narratives addressed are those of Workers, Exodus and Genesis, thought by the photographer himself as his great works.
Keywords: Geography; Fotography; Sebastião Salgado